Misperception of Chance, Conjunction, Belief in the Paranormal and Reality Testing: A Reappraisal. Issue 5 (5th August 2014) - Dagnall, Neil; Drinkwater, Kenneth; Parker, Andrew; Rowley, Kevin
Summary The present study examined the degree to which specific probabilistic biases (misperception of chance and conjunction fallacy) were associated with belief in the paranormal and proneness to reality testing (RT) deficits. Participants completed measures assessing probabilistic reasoning, belief in the paranormal and RT. Perception of randomness predicted the level of paranormal belief and proneness to RT deficits. These results provide support for the notion that paranormal believers demonstrate greater misrepresentation of chance. With regard to conjunction, a framing effect occurred. Problems presented in a paranormal context correlated negatively with the level of paranormal belief and proneness to RT deficits. Copyright © 2014 John Wiley & Sons, Ltd.